1.5°C Too Soon : More Must Be Done - Sembiring, Margareth (2018)
The latest IPCC special report released in early October 2018 estimated that global temperature increase may reach 1.5°C anytime between 2030 and 2050. This is much sooner than the end of the century timeframe set in the 2015 Paris Agreement. Will this report lead to more ambitious and aggressive emission mitigation efforts?